PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN BANK SAMPAH DI KECAMATAN AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA - Anjasmari, Ni Made Musiyani (PPPM STIA Amuntai, 2020)
The problem of waste management that is not good in Amuntai City is due to the lack of socialization of related institutions namely the Department of Housing, Settlement Areas, and the Environment of North Hulu Sungai Regency, causing a lack of public awareness in managing waste, community consumption patterns have not led to insightful patterns environment, the use of packaging in the form of paper, plastic bags, cans, etc., resulting in a pile of garbage outside the Temporary Disposal Site (TPS) and the lack of a Temporary Disposal Site (TPS). With the presence of the garbage bank program, the community can reuse household waste produced so that it has economic value, by selling it to the garbage bank. The purpose of this research is to identify and analyze community empowerment in the management of waste banks in Amuntai Tengah Sub-District, Hulu Sungai Utara Regency and to identify and analyze supporting factors and inhibiting factors for community empowerment in waste bank management in Amuntai Tengah District that are fostered by the Department of Housing, Regions Settlement and Environment of North Hulu Sungai Regency. The research method is descriptive qualitative, the type and source of data is primary data through observation, interviews while secondary data through documents that exist in the Trash Bank in Amuntai Tengah District, the technique used in sampling is Snow Ball sampling technique (snowball sampling) ). From the results of the study showed that community empowerment in managing the waste bank has been carried out well through the activities carried out namely the existence of Desire, Trust, Confidence, Credibikitas / Encouragement, Responsibility and Communication in running the garbage bank Unit in the Amuntai Tengah District. Supporting factors are adequate waste sorting places and tools in grinding used vegetables and leaves to make compost, while the inhibiting factor is the lack of facilities and infrastructure, which is inadequate transportation equipment and the absence of tools for counting or refining plastic waste and tools cardboard presses and lack of funds to run a waste bank management As for the advice given for input to the waste bank, they include the introduction of waste sorting and how to manage the Waste Bank, the provision of appropriate transportation facilities as well as providing garbage counting equipment and cardboard pressing equipment for recycling.